ABOUT DISSIPATION PROPERTIES OF MULTI-STOREY RC FRAME BUILDINGS OF LARGE-SCALE-CONSTRUCTION PROJECTS AT THEIR EARTHQUAKE-RESISTANCE ESTIMATION - Aleksei Victorovich Sosnin (Современная наука и инновации, 2022)
Factor characterized a dissipation energy capability of multi-story RC large-scale construction buildings in the Response Spectrum Method formulation are considered in the article. It is suggested for their earthquake-resistance shortage estimation for demand spectrum a viscous damping ξel to calculate with a value of fundamental period Ti and total damping ξeff with an actual working lifespan. As a tool-feature is used energy dissipation technique of the Capacity Spectrum Method procedure ‹A›, which has been realized in the software SAP2000. An adjusted value of damping modification factor KΨ for SP 14.13330.2014 computational estimation is offered for research objects.